Environment Friendly Coffee Shop Intentions: How Does Peer Pressure Mediate Among Millennials? - Genoveva, Genoveva; Adinda, Salwa; Kartawaria, Filbertha Nathania (Jurnal Manajemen Indonesia, 2023)
This study aims to determine whether these products are environmentally friendly among millennials. The millennial generation occupies the second-largest position in coffee consumption. The above statement shows the importance of Indonesia focusing more on millennial consumers as a large and potential market for environmentally friendly products. This study aims to determine whether the product is environmentally friendly; in this case, the green coffee shop affects consumer buying interest with Peer Pressure as the mediating variable. This study used non-purposive sampling with snowball techniques. The questionnaire data was tested using Partial Least Square (PLS) from 255 millennial respondents in Indonesia. The results showed that Environmental Knowledge, Environmental Awareness, Social Values, and Eco-Friendly Labels influence Green Purchase Intention through Peer Pressure as an intervening variable. Thus, it can be said that millennial consumers positively influence environmentally friendly products to increase consumer buying interest further. In addition, our results also show that Peer Pressure mediates the relationship between Environmental Knowledge, Environmental Awareness, Social Values, and Green Labels on Green Purchase Intentions of millennial consumer groups in Indonesia. Keywords— Green Marketing; Green Purchase Intention; Peer Pressure; Social Value